Stress distribution of overdenture using odd number implants – A Finite Element Study. (October 2019) - Kasani, Rahul; Rama Sai Attili, Bhaskar Krishna; Dommeti, Vamsi Krishna; Merdji, Ali; Biswas, Jayanta Kumar; Roy, Sandipan
Abstract: The objective of this study is to look at stress patterns actuated by locator connections when used to hold mandibular overdentures retained by odd number implants. Two 3D models were prepared to simulate mandibular Implant overdentures retained by three and five Implants. The geometric solid models were modelled in solid modelling software, the models were then assembled and analysed. Three different vertical loads 50N, 100N and 150N were applied on the overdenture. Stresses were assessed at the areas of implant and connection parts, Mucosa hidden overdentures, and cortical and cancellous bone adjoining the implants. The results of this examination demonstrated that the Von Mises stresses produced by applying vertical load differed by the number of Implants used to retain the overdenture. It has been observed that maximum von misses stress induced in the implant complex and the stress induced in the mucosa layer was very low. The adaptability of the overdenture material assumed a noteworthy job in circulating the load stress and twisting of all basic structure. Stress induced in overdenture is higher in three-implant when compared to five-implant retained overdenture. The stresses induced in overdenture in two models were investigated under different loading conditions, five different combinations of the bone quality and it was found that in all the cases the maximum stress has been concentrated in the implant complex, and stress induced in overdenture is low in the case of five implant retained overdenture.